2003
DOI: 10.1099/mic.0.26113-0
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational processing of the xylanase Xys1L from Streptomyces halstedii JM8 is carried out by secreted serine proteases

Abstract: The xylanase Xys1L from Streptomyces halstedii JM8 is known to be processed extracellularly, to produce a protein of 33?7 kDa, Xys1S, that retains catalytic activity but not its cellulose-binding capacity. This paper demonstrates that at least five serine proteases isolated from Streptomyces spp. have the ability to process the xylanase Xys1L. The genes of two of these extracellular serine proteases, denominated SpB and SpC, were cloned from Streptomyces lividans 66 (a strain commonly used as a host for protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Similarly, the genes encoding chitinases were cloned and sequenced from alkaliphilic actinomycete, Nocardiopsis prasina OPC-131 into Escherichia coli [11]. FernandezAbalos et al [12] demonstrated the post translational processing of the xylanase Xys1L from Streptomyces halstedii JM8 by secreted alkaline serine protease. Recently, a novel calcium independent serine protease from an alkaliphilic bacterium, Nesterenkonia sp.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the genes encoding chitinases were cloned and sequenced from alkaliphilic actinomycete, Nocardiopsis prasina OPC-131 into Escherichia coli [11]. FernandezAbalos et al [12] demonstrated the post translational processing of the xylanase Xys1L from Streptomyces halstedii JM8 by secreted alkaline serine protease. Recently, a novel calcium independent serine protease from an alkaliphilic bacterium, Nesterenkonia sp.…”
Section: Introductionmentioning
confidence: 99%
“…This processing was almost completely inhibited when the serine protease inhibitor slpI gene from S. lividans was co-expressed with the xylanase xysA gene in S. lividans. In contrast, none of these proteases was able to process Xyl30 in vitro [10].…”
Section: Introductionmentioning
confidence: 88%
“…plasmid, obtaining pSHA2vo, v1, v2, v3, v4 and v5. Then, all amplifications were cloned into the E. coli/Streptomyces shuttle vector pN702GEM3 [10] in a triple ligation to construct the xysA derivatives: HindIII/BglII fragment from pN702GEM3 ? BglII/XhoI fragment from pXHis1 [1] ?…”
Section: Plasmid Constructionsmentioning
confidence: 99%
“…To construct pNGEM/OriT/P we utilized the E. coli – Streptomyces shuttle vector pN702GEM3. pN702GEM3 (Fernandez-Abalos et al, 2003) contains the pIJ702 origin of replication (for Streptomycetes), the bifunctional Neo/Kan resistance marker from Tn 5 (for both E. coli and Streptomycetes), the pUC origin of replication (for E. coli ) and a polylinker derived from pGEM3Zf(+) (Promega). This vector is replicative but not conjugative in Streptomycetes.…”
Section: Methodsmentioning
confidence: 99%